The Role of State-Owned Enterprises in Supporting Indonesia's National Development - Siregar, Sheila Ananda; Syahputra, Muhammad Daffa; Tjipto, Frederick Xaverius; Pranoto, Ananda Bima Al Wajdi Majid; Susanto, Jocelyn Phebelia; Hutagaol, Nadya Elisa; Jefferson, Gilbert; Sitorus, Rolib (Formosa Journal of Applied Sciences, 2024)
The purpose of this study is to determine the role of State-Owned Enterprises (BUMN) in supporting national development in Indonesia, especially in achieving the objectives of the 2005-2025 National Long-Term Development Plan (RPJPN) and the Sustainable Development Goals (SDGs) agenda, to determine the challenges faced by BUMN in terms of governance, transparency, and innovation that can affect their effectiveness in driving national economic growth and equitable development, and to determine BUMN strengthening national economic resilience and increasing the competitiveness of local industries, especially in strategic sectors such as energy, transportation, telecommunications, and banking. Research methods that can be used include qualitative and quantitative approaches, as well as literature studies and document analysis. The qualitative approach allows researchers to gain in-depth insights into the practices and challenges faced by BUMN. The expected result is that BUMN is an important pillar in Indonesia's national development.